Upaya Preventif melalui Pemeriksaan Gigi dan Sikat Gigi Massal di SDN 2 Lainungan - Dirman, Rezki; Arsad, Arsad; Zulkaidah, Utari; Yasin, Sultan Amin; Yulistina, Yulistina (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Dental and oral diseases, especially caries and periodontal disease, are still widely suffered, both by children and adults. Prevention (preventive) can be defined as preventing the onset or development of a disease or restoring bodily functions that have been lost. This activity aims to improve the knowledge and skills of brushing teeth properly and correctly in students as well as checking dental and oral hygiene and doing mass brushing. After the dental examination, they were motivated to perform fillings on teeth that had caries and carry out dental health education activities. The trick is to do a demonstration of brushing your teeth and continue with the practice of brushing your teeth together using a toothbrush and toothpaste.  The conclusion of this service activity is that there is an increase in knowledge and behavior of maintaining dental and oral health after being given dental health education. Health promotion activities and demonstrations on how to brush their teeth properly and correctly can increase students' knowledge and awareness in maintaining healthy teeth and mouth.